Construction and osteogenic effects of 3D-printed porous titanium alloy loaded with VEGF/BMP-2 shell-core microspheres in a sustained-release system - Liu, Zheng; Xu, Zhenchao; Wang, Xiyang; Zhang, Yilu; Wu, Yunqi; Jiang, Dingyu; Jia, Runze (Frontiers in Bioengineering and Biotechnology, 2022)
The repair and reconstruction of bone defects remain a challenge in orthopedics. The present study offers a solution to this problem by developing a vascular endothelial growth factor (VEGF)/ bone morphogenetic protein 2 (BMP-2) shell-core microspheres loaded on 3D-printed porous titanium alloy via gelatin coating to prepare a titanium-alloy microsphere scaffold release system. The composite scaffold was characterized via scanning electron microscope (SEM) and energy disperse spectroscopy (EDS), and the effect of the composite scaffold on the adhesion, proliferation, and differentiation of osteoblasts were determined in vitro. Furthermore, a rabbit femoral defect model was established to verify the effect of the composite scaffold on osteogenesis and bone formation in vivo. The results demonstrated that the composite scaffold could release VEGF and BMP-2 sequentially. Meanwhile, the composite scaffold significantly promoted osteoblast adhesion, proliferation, and differentiation (P < 0.05) compared to pure titanium alloy scaffolds in vitro. Furthermore, the composite scaffold can exhibit significant osteogenic differentiation (P < 0.05) than gelatin-coated titanium alloy scaffolds. The in vivo X-rays demonstrated that the implanted scaffolds were in a good position, without inflammation and infection. Micro-CT and quantitative results of new bone growth illustrated that the amount of new bone in the composite scaffold is significantly higher than that of the gelatin-coated and pure titanium alloy scaffolds (P < 0.05). Similarly, the fluorescence labeling and V-G staining of hard tissue sections indicated that the bone integration capacity of the composite scaffold was significantly higher than the other two groups (P < 0.05). This research suggests that VEGF/BMP-2 shell-core microspheres loaded on 3D-printed titanium alloy porous scaffold through gelatin hydrogel coating achieved the sequential release of VEGF and BMP-2. Most importantly, the in vitro and in vivo study findings have proven that the system could effectively promote osteogenic differentiation and osseointegration.